Composite Micro-Mesoporous Materials As Catalysts For The Production Of Liquid Fuels From Catalytic Cracking Of Fatty Acids Mixture And Used Palm Oil - Ooi, Yean Sang (2004)

(untitled)
Campuran asid-asid lemak daripada minyak kelapa sawit (F AM) serta minyak kelapa sawit terpakai (UPO), merupakan sumber yang murah dan boleh diperbaharui telah diterokai untuk penghasilan bahan api cecair daripada proses peretakan bermangkin. Proses peretakan bermangkin ini dikaji pada tekanan atmosfera dalam reaktor mikro, pada suhu tindakbalas 723 K dan halaju ruang (WHSV) pada 2.5 jam-I. Mangkin ZSM-5 berliang mikro dengan nisbah Si/AI yang berbeza dan zeolit Beta, aluminosilikat berliang meso serta bahan komposit berliang mikro-meso telah digunakan sebagai mangkin peretakan. Palm oil based fatty acids mixture (F AM) and used palm oil (UPO), low cost and renewable resources were explored for the production of liquid fuel using catalytic cracking process. The catalytic cracking reaction was studied at atmospheric pressure in a fixed bed micro-reactor at reaction temperature of 723 K and weight hourly space velocity (WHSV) of 2.S h- 1 • Microporous ZSM-S catalyst with different Si/ Al ratios and zeolite Beta, mesoporous aluminosilicates and composite micro-mesoporous materials were used as cracking catalysts.